Spatial impact of urban expansion on lake surface water temperature based on the perspective of watershed scale - Tang, Linfeng; Yang, Kun; Shang, Chunxue; Peng, Zongqi; Luo, Yi (Frontiers in Environmental Science, 2022)
As an important ecological environmental factor, the lake water surface temperature (LSWT) has an important impact on the ecological diversity of lakes and watersheds. With the acceleration of urbanization in China, the impact of urban expansion on LSWT can not be ignored. In this study, we introduced the spatial influence(G) equation, selected MOD11A2, impervious surface (IS), digital elevation model (DEM) and Landsat series remote sensing images as data sources, and took six lakes with rapid urban expansion in China as the empirical research object to explore the variation characteristics of urban expansion and LSWT in six lake watersheds and the spatial influence of urban expansion on LSWT. Finally, the following conclusions can be drawn: The results show that 1) The IS in the six watersheds all experienced significant expansion, with an increase of 1.80–3.91 times. 2) From the annual average LSWT from 2001 to 2018, only Poyang Lake’s LSWT-night shows a cooling trend, while other lakes, whether LSWT-day or LSWT-night, show a warming trend. 3) G is used to comprehensively consider the area change of IS in the watershed, the influence of distance and the change of lake area, which can quantify the impact of IS on LSWT, so as to further explain and describe the spatial influence process and characteristics of IS expansion on LSWT.